Combination of AKT inhibitor ARQ 092 and sorafenib potentiates inhibition of tumor progression in cirrhotic rat model of hepatocellular carcinoma - Jilkova, Zuzana Macek (Oncotarget, 2018)
The prognosis of patients with advanced hepatocellular carcinoma (HCC) is very poor. The AKT pathway is activated in almost half of HCC cases and in addition, long term exposure to conventional drug treatment of HCC, sorafenib, often results in over-activation of AKT, leading to HCC resistance. Therefore, it is important to assess the safety and the efficacy of selective allosteric AKT inhibitor ARQ 092 (Miransertib) in combination with sorafenib. Here, we demonstrated in vitro that the combination of ARQ 092 with sorafenib synergistically suppressed proliferation, promoted apoptosis, and reduced migration. To test the effect of the combination in vivo, rats with diethylnitrosamine-induced cirrhosis and fully developed HCC were randomized and treated with vehicle, sorafenib, ARQ 092 or the combination of ARQ 092 with sorafenib; (n=7/group) for 6 weeks. Tumor progression, size of tumors and the mean tumor number were significantly reduced by the combination treatment compared to the control or single treatments. This effect was associated with a significant increase in apoptotic response and reduction in proliferation and angiogenesis. Sirius red staining showed a decrease in liver fibrosis. Moreover, treatments improved immune response in blood and in tumor microenvironment. Thus, the combination of ARQ 092 with sorafenib potentiates inhibition of tumor progression and gives the possibility of therapeutic improvement for patients with advanced HCC.